Sphaeropsidones, Phytotoxic Dimedone Methyl Ethers Produced by Diplodia cupressi: A Structure−Activity Relationship Study - Evidente, Antonio; Maddau, Lucia; Scanu, Bruno; Andolfi, Anna; Masi, Marco; Motta, Andrea; Tuzi, Angela (Journal of Natural Products, 2011)
Sphaeropsidone and episphaeropsidone are two phytotoxic dimedone methyl ethers produced by Diplodia cupressi, the causal agent of a canker disease of cypress in the Mediterranean area. In this study, eight derivatives obtained by chemical modifications and two natural analogues were assayed for phytotoxic and antifungal activities, and a structure?activity relationship was examined. Each compound was tested on nonhost plants and on five fungal pathogenic species belonging to the genus Phytophthora. The results provide insights into structure?activity relationships within these compounds. It was found that the hydroxy group at C-5, the absolute C-5 configuration, the epoxy group, and the C-2 carbonyl group appear to be structural features important in conferring biological activity. The conversion of sphaeropsidone into the corresponding 1,4-dione derivative led to a compound showing greater antifungal activity than its precursor. This finding could be useful in devising new natural fungicides for practical application in agriculture.
doi: 10.1021/np100837rdoi: 10.1021/np100837rThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: antifungal activity (voyant); Diplodia cupressi; Phytotoxicity; Sphaeropsidones

Behaviour of different horticultural species in phytotoxicity bioassays of bark substrates - Ortega, M C; Moreno, M T; Ordovas, J; Aguado, M T (Scientia Horticulturae, 1996)
The use of forestry wastes (barks, sawdust, wood chips) as potting media components can involve serious problems of toxicity that must be evaluated. Evaluation methods may consist of analytic techniques to detect and quantify phytotoxic molecules, or rapid bioassays, with low technical requirements, using species sensitive to the toxic elements. These bioassays should be able to predict plant behaviour in real growing conditions. In this study we used as substrate cork oak bark (Quercus suber L.). This material, like other forestry wastes, contains phytotoxic phenolic compounds which can be washed out with hot water. The phenolic content of cork (C) and washed cork (WC) was measured, and two germination bioassays were carried out with eight horticultural species. In the first, aqueous extracts of cork (C) and washed cork (WC) obtained with water at 15°C and 70°C were used, and the second was done directly on the substrates. In addition, a seedling growing test was carried out with the same species. We concluded that tomato and lettuce are the most sensitive species, and the direct test on the substrate is recommended owing to its simplicity and close correspondence to growing conditions.
Keywords: Barks; Bioassay; Cork; Horticultural; Phenolic acids; Phytotoxicity; substrate